Testimonial rallies and the construction of memetic authenticity. (April 2018) - Shifman, Limor
This article traces the role of 'testimonial rallies' – Internet memes in which participants post personal photos and/or written accounts as part of a coordinated political protest – in the formulation of truth-related values. Rather than endorsing the value of truth per se, rallies such as 'We are the 99 percent' or 'I never ask for it' valorize what I term 'memetic authenticity'. This construction of the authentic incorporates four basic components: evidence, self-orientation, affective judgement, and mimesis. By combining 'external authenticity' that relates to the aggregation of factual proofs with forms of 'internal authenticity' that focus on emotive individual experiences, testimonial rallies serve as a grassroots weapon of the weak against those in power. While 'external' and 'internal' forms of authenticity are happily married in this genre, I conclude with a reflection on our grim future in the case of divorce.